2007
DOI: 10.1007/s10641-007-9272-z
|View full text |Cite
|
Sign up to set email alerts
|

Lake trout (Salvelinus namaycush) spawning behaviour: the evolution of a new female strategy

Abstract: A video camera inside an underwater housing was used to record the spawning activities of lake trout, Salvelinus namaycush, in Kushog Lake, Ontario (Canada). Contrary to the commonly accepted belief describing lake trout as the only salmonine to spawn exclusively at night, the recordings were taken during the day. Lake trout spawning behaviour is described in detail and compared with other salmonine species. The loss of female "nest-building" and assumption of a novel itinerant strategy during which females tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…In rainbow trout, Su et al (1996) suggested Effects of inbreeding on sperm quality that a lack of detection of inbreeding depression on male fertilization success could be attributed to low levels of inbreeding in their study. Accordingly, our results are consistent with those of Zajitschek et al (2009), despite the markedly different systems of mating and sexual selection between the two species (Gunn, 1995;Esteve et al, 2008;Zajitschek and Brooks, 2010). In a study on guppies by Zajitschek et al (2009), four generations of brother-sister matings (F = 0.59) were required to detect any evidence of inbreeding depression on sperm competitiveness.…”
Section: Discussionsupporting
confidence: 87%
“…In rainbow trout, Su et al (1996) suggested Effects of inbreeding on sperm quality that a lack of detection of inbreeding depression on male fertilization success could be attributed to low levels of inbreeding in their study. Accordingly, our results are consistent with those of Zajitschek et al (2009), despite the markedly different systems of mating and sexual selection between the two species (Gunn, 1995;Esteve et al, 2008;Zajitschek and Brooks, 2010). In a study on guppies by Zajitschek et al (2009), four generations of brother-sister matings (F = 0.59) were required to detect any evidence of inbreeding depression on sperm competitiveness.…”
Section: Discussionsupporting
confidence: 87%
“…However, use of manual stripping as a surrogate for egg deposition during spawning is a source of bias in our study. Although we did our best to approximate normal egg deposition by holding the trout in a natural spawning posture (that is, head and tail flexed slightly upwards) [33,34] during stripping, we do not know to what extent physical forces applied to the eggs and oviduct transmitter during manual stripping represent those present during natural egg deposition. If force applied during manual stripping was greater than would be present during spawning, our results could overestimate transmitter expulsion rate.…”
Section: Discussionmentioning
confidence: 99%
“…The ovulating trout were removed from the holding tank one at a time and anesthetized as before to prevent excessive stress. Anesthetized trout were held dorsal side up with heads and tails pointed slightly upward, as occurs during natural egg deposition [33,34]. Their bellies were then massaged from anterior to posterior until the oviduct tag was expelled, or the trout stopped expelling eggs.…”
Section: Retention and Expulsion Of Oviduct-inserted Transmittersmentioning
confidence: 99%
“…Preferred spawning sites are rocky shoals, devoid of vegetation, and the fish will habitually return to the same site each year. [55][56][57][58][59][60][61] This behavior is the key that allows lidar to locate their spawning sites and is also why knowledge of the location of their spawning sites is of such importance in controlling their population.…”
Section: Signal-to-noise Ratio and Signal-to-backgroundmentioning
confidence: 99%